Answer:
a = - 4, b = 5
Step-by-step explanation:
Expand the left side and compare the coefficients of like terms on the right side.
- 3(2x² + ax + b)
= - 6x² - 3ax - 3b
Comparing like terms with - 6x² + 12x - 15
x - term → - 3a = 12 ( divide both sides by - 3 )
a = - 4
constant term → - 3b = - 15 ( divide both sides by - 3 )
b = 5
Answer:
c
Step-by-step explanation:
2 would be the answer. Replace the x with the three and multiply that with the 2 and then subtract 4.
I believe the right anwser is c